Narratives of Compulsory Heterosexuality Struggles of Filipino Lesbians in the Selected Poems from Tingle: Anthology of Pinay Lesbian Writings - Barrera, Kenneth Ian (Randwick International of Education and Linguistics Science Journal, 2024)
Utilizing Adrienne Rich's concept of compulsory heterosexuality, this research investigates narratives and struggles of Filipina lesbians as depicted in selected poems from "Tingle: Anthology of Pinay Lesbian Writings." Rich's theory, which describes heterosexuality as a social imperative and not an option available to women, can serve as a critical lens to understand Filipino literature more fully. This research exposes the profound effect of Rich's conception of society on the lived experiences of LGBTQIA+ community members in the Philippines. Through careful investigation using qualitative content analysis, themes of social pressure, economic dependence, and compulsory heterosexuality become evident. The findings underlined the urgency of acknowledging and challenging these deeply entrenched struggles, drawing attention to the potential damage imposed by societal norms and perceptions that persist over time. The conclusion of this research calls for greater inclusivity, representation, and support of the LGBTQIA+ community. Institutions across various sectors should actively foster understanding, acceptance, and celebration of diverse narratives to enrich the human experience.